Considerations sur la ramification de L'aorte abdominale du hamster (Mesocricetus Auratus) - Orsi, A. M.; Pinto Silva, E. P.; Mello Dias, S.; Oliveira, M. C. (My University, 1977)
The disposition of the abdominal aorta branching in Mesocricetus auratus is described, establishing variation groups with relation to the celiac, cranial mesenteric, renal, genital and caudal mesenteric arteries. Sixty animals (30 males and 30 females) of different ages and weights, were anesthetized with chloroform, injected with contrasting substance in the abdominal aorta (50 animals with Neoprene latex and 10 with a radioopaque mass), after which they were dissected with the help of a stereoscopic microscope. The animals with radioopaque masses were radiographed in comparison with the other animals. The results are expressed in relative percentage figures and compared with other mammalian arterial dispositions.
Considerations about the branching of the aorta abdominalis in hamster (Mesocricetus auratus)
Keywords: abdominal aorta; normal value; animal; female; guinea pig; hamster; histology; iliac artery; male; mesenteric artery; rabbit; renal artery; Animal; Aorta, Abdominal; English Abstract; Female; Guinea Pigs; Hamsters; Iliac Artery; Male; Mesenteric Arteries; Mesocricetus; Rabbits; Renal Artery